2015
DOI: 10.5539/gjhs.v8n5p110
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation on the Status of Implementation of Communications and Information Management System (MCI) in Khorasan Razavi Hospitals

Abstract: Background and Objectives:The aim of this investigation is to determine the mean scores of the possibility of implementing the MCI standards in Khorasan Razavi hospitals, from the perspective of Managers, in order to provide a suitable model for evaluating and promoting the system.Methods:This was a Research and method (R&D) and Survey Research method, which is of the type of Cross- Sectional, descriptive-analytic Studies conducted in two steps in hospitals of Khorasan Razavi from July to December 2014. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The information we received assisted in improving friendliness of the web application to users. As a recommendation from previous studies, the design of nursing information or record systems should be properly aligned to the expectations and needs of targeted users (Moghaddasi et al, 2017; Shojaei et al, 2015). Otherwise, users will not accept the developed system and its adoption may be difficult to succeed.…”
Section: Discussionmentioning
confidence: 99%
“…The information we received assisted in improving friendliness of the web application to users. As a recommendation from previous studies, the design of nursing information or record systems should be properly aligned to the expectations and needs of targeted users (Moghaddasi et al, 2017; Shojaei et al, 2015). Otherwise, users will not accept the developed system and its adoption may be difficult to succeed.…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that the design of a health information system must fully match users' practices and must support them as they undertake their tasks; otherwise, the system will not be accepted by users or its uptake could face difficulties [ 21 ]. Among the criteria related to ‘suitability for the task,’ disagreement was mainly found for the factors of ‘easy to find required commands’ and ‘finding necessary information on a given screen.’ This is in line with the findings of Rogers et al [ 17 ], which showed that nurses are occasionally unable to complete a task due to navigation issues and difficulties in finding the required functions.…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, the systems could make difficulties and negatively impact users' practice [29]. One way to overcome this challenge is to familiarize nursing managers with the features of nursing management information systems.…”
Section: Reportingmentioning
confidence: 99%